(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Acetonic extracts of Akanda was tested against different parameters of the life cycle of Cryptolestes pusillus. The lowest and highest oviposition rate (0.89±0.26 and 2.67±0.33 egg/female/day), hatching rate (14.67±0.53 % and 51.11±0.59 %), adult emergence (16.89 % and 40.89 %), and longevity (male 64.78±1.01day and 105.67±1.09 day) and female (69.56 ± 0.38 day and 113.22±0.57 day) were found in doses (552.413 and 163.678?gcm-2) whereas in control they were 4.89±0.35 egg/female/day, 91.22±1.02 %, 88.44 %, 156.11±1.37 day and 169.67±2.52 day respectively. But highest and lowest incubation period (7.33±0.33 day and 4.89±0.35 day) and developmental period (71.67±0.60 and 39.89±0.26 days) occurred in the same doses and in control these are 4.11±0.26 egg/female/day and 33.44±0.50days. Bangladesh J. Sci. Ind. Res. 42(2), 157-162, 2007